2016
DOI: 10.1111/omi.12175
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of de‐N‐acetylase PgaB from periodontopathogen Aggregatibacter actinomycetemcomitans

Abstract: The oral pathogen Aggregatibacter actinomycetemcomitans uses pga gene locus for the production of an exopolysaccharide made up of a linear homopolymer of β-1,6-N-acetyl-d-glucosamine (PGA). An enzyme encoded by the pgaB of the pga operon in A. actinomycetemcomitans is a de-N-acetylase, which is used to alter the PGA. The full length enzyme (AaPgaB) and the N-terminal catalytic domain (residues 25-290, AaPgaBN) from A. actinomycetemcomitans were cloned, expressed and purified. The enzymatic activities of the Aa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…The PNAG deacetylase enzyme PgaB of A. actinomycetemcomitans has been characterized previously in our laboratory and we showed that the N‐terminal catalytic domain of PgaB is responsible for the deacetylase activity . The results reported here indicate that in the absence of the catalytic domain of PgaB, the pga operon transcription ( pgaA , pgaB and pgaC ) is downregulated, which leads to less PNAG production.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The PNAG deacetylase enzyme PgaB of A. actinomycetemcomitans has been characterized previously in our laboratory and we showed that the N‐terminal catalytic domain of PgaB is responsible for the deacetylase activity . The results reported here indicate that in the absence of the catalytic domain of PgaB, the pga operon transcription ( pgaA , pgaB and pgaC ) is downregulated, which leads to less PNAG production.…”
Section: Discussionsupporting
confidence: 56%
“…The protein sequence of Aa PgaB is very similar to that of Ec PgaB and the structures are highly superimposable . In E. coli , the non‐polar ΔpgaB strain was shown to be unable to export PNAG although they were able to produce PNAG .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other poly-β-1,6-GlcNAc de- N -acetylases with solved X-ray structures, so far, are Ad IcaB from Ammoniex degensii [ 77 ], Bb BpsB from Bordetella bronchiseptica [ 45 ], and Aa PgaB from Aggregatibacter actinomycetemcomitans [ 147 ]. All of these enzymes show low activity on β-1,6-glucan, a common property of this enzyme subclass within family CE4.…”
Section: Ce4 Enzymes Active On Chitooligosaccharides and Their Submentioning
confidence: 99%
“…Acetylxylan esterases from S. lividans and C. thermocelum [ 74 ] show the canonical active topology and metal coordination in this enzyme family, as well as other peptidoglycan deacetylases ( S. mutants [ 74 ], B. anthracis [ 69 ], and B. cereus [ 150 ]). The case of poly-β-1,6-GlcNAc deacetylases is different [ 75 , 76 , 77 , 147 ], as they have a circularly permutated CE4 domain and some variations in the positioning of active site residues, as discussed below. It was not until 2014 that the first crystal structure of a CE4 enzyme in complex with substrates was solved, that of the Vibrio cholera CDA [ 62 ], providing new information on loop organization and insights into the structural determinants of substrate binding, specificity, and catalysis.…”
Section: Structural and Sequence Features Of Ce4 Enzymes Active Onmentioning
confidence: 99%